Pelatihan Pembuatan Modul Ajar Berbasis Pembelajaran Inklusi bagi Guru-Guru SMAN 2 Tapung Hilir - Asnawi, Asnawi; Mukhlis, Muhammad; Nur, Hidayatun; Febria, Rhani (UIR Press, 2026)
Teaching modules are a crucial component of education. Therefore, teachers are required to have the ability to design and create teaching modules tailored to student needs. The designed teaching modules should also consider inclusive learners. A fundamental problem currently occurring is the lack of understanding and knowledge among teachers on how to create inclusive-based teaching modules at SMAN 2 Tapung Hilir. Therefore, teachers need to revise the design of learning modules. This aims to accommodate the needs of inclusive learning in schools for the sake of equitable education for students. Based on the results of the activity, it can be seen that SMAN 2 Tapung Hilir teachers have the knowledge and skills to design and provide learning for inclusive learners in every subject.